Clinical Characteristics and Etiology of Terminal Ileum Ulcers: A Retrospective Study - Tseveldorj, Nomingerel; Gündüz, Cemre; Saracoğlu, Yaşar Ozan; Dağlı, Ülkü (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Terminal ileal ulcers can have various etiologies, including Crohn’s disease (CD), infections, and medication-related causes. This study aims to investigate the incidence of terminal ileal ulcers detected during colonoscopies, explore their underlying causes, and analyze their clinical, endoscopic, and histopathological characteristics. Additionally, the study aims to identify predictive factors that indicate the need for follow-up. Materials and Methods: Medical records of all patients who underwent colonoscopies, between 2009 and 2019 were retrospectively reviewed. Patients with terminal ileal ulcers, with or without ileocecal valve involvement, were included in the study. Demographic information, medication usage, symptoms, colonoscopy findings, and histopathological data of these patients were analyzed. Results: A total of 398 patients were included in the study. Histopathological examination revealed that 243 patients (61%) had active ileitis, and 69 patients (17.4%) had chronic active ileitis. The final diagnoses for ulcers were: nonspecific ulcers in 212 patients (53.3%), CD in 66 patients (16.6%), and non-steroidal anti-inflammatory drug-induced ulcers in 58 patients (14.6%). In the multivariate analysis, the parameters predicting CD included the presence of 10 or more ulcers (odds ratio (OR) = 7.305), deep ulcers (OR = 7.431), and edematous surrounding tissue (OR = 5.174), all of which were statistically significant (P < .001). Conclusion: Upon final evaluation, only 66 patients (16.6%) were diagnosed with CD, while 212 patients (53.3%) had nonspecific ulcers. The majority of patients with healed ulcers exhibited pathological findings consistent with active ileitis. Therefore, it can be concluded that not all terminal ileal ulcers are indicative of CD. In those cases with active ileitis, repetitive colonoscopies should be reconsidered. Cite this article as: Tseveldorj N, Gündüz C, Saracoğlu YO, Dağlı Ü. Clinical characteristics and etiology of terminal ileum ulcers: A retrospective study. Turk J Gastroenterol. 2024;35(8):609-617.